hubungan Aktifitas Fisik, Kebiasaan Makan, Dan Riwayat Keluarga Dengan kejadian Dismenore Primer Pada Mahasiswi Angkatan 2021 Fikes Uhamka Tahun 2025 - Maharani, Giska (Universitas Veteran Bangun Nusantara, 2025)
Primary dysmenorrhea refers to menstrual pain without any underlying organic disorder, commonly experienced by young women, which can affect their daily activities and quality of life. This study aimed to determine the relationship between physical activity, eating habits, and family history with the incidence of primary dysmenorrhea among the 2021 cohort students of the Faculty of Health Sciences, Muhammadiyah University Prof. Dr. HAMKA in 2025. This research applied a quantitative method with a cross-sectional design involving 105 respondents selected through proportional random sampling. Data were collected using an online questionnaire that had been tested for validity and reliability, and analyzed using the Chi-Square test with a significance level of 0.05. The results indicated no significant association between physical activity (p=0.180), eating habits (p=1.000), and family history (p=0.180) with the incidence of primary dysmenorrhea. However, respondents with lower physical activity, unhealthy dietary patterns, and a positive family history tended to experience a higher proportion of menstrual pain. These findings highlight that lifestyle factors remain important components of promotive and preventive efforts to support female students’ reproductive health. Keywords: Physical Activity, Dysmenorrhea, Eating Habits